Fatores associados ao relato de violência interna no trabalho em unidades do Sistema Municipal de Saúde de Belo Horizonte - Luiza Oliveira Lignani (2015)
The escalation of violence in health care facilities is a worldwide phenomenon that adversely compromises the health of workers and the general population. Workplace violence is associated with illness, absenteeism, reduced performance and high turnover. Such situations can weaken teams of health workers, resulting in damage to the quality of service. Thus, conducting research focusing on factors associated with violence at work are required to identify areas in developing prevention plans. This research seeks to give visibility to the phenomenon in the SUS-BH, providing data on the frequency of violence at work, the characteristics of workers and working conditions. The purpose of this research is to know the proportion of workers who experienced violent acts during the performance of work activities and identify the association of such reports with the working conditions. It is a cross-sectional survey conducted from September 2008 to January 2009, with a sample of 2.205 workers in the municipal health department of Belo Horizonte. We used the Epi Info® software, version 6.0, for the random selection of the sample subjects, considering geographical location of the health facility, type of occupation and level of care. The following questions were used to build the variable reporting of workplace violence: a) In the last 12 months, there was an episode of aggression or threat practiced by their bosses or co-workers to service users (during your work) ?; b) In the last 12 months, there was an episode of aggression or threat practiced by their bosses or co-workers to another co-worker (during your work)? It was verified the association between workplace violence and the explanatory variables: sociodemographic characteristics, job characteristics and working characteristics: environment / materials (temperature, noise, ventilation, furniture, lighting and equipment); and social support. Associations were estimated by calculating prevalence ratios (PR), considering a confidence interval of 95 % in univariate analysis. Variables with p-value 0.20 were included in multivariate analysis using Poisson Regression with robust variance. Found 31.5 % report of workplace violence in the last year (between colleagues or between worker and user). Occupy university-level job position (1.24); working in emergency room (PR = 1.61) and in primary health care (PR = 1.50); report unsatisfactory situation regarding the environment / working materials (PR = 1.25) and reporting low social support (PR = 1.54) were positively associated with the event of interest (p = 0.05). We suggest the implementation of violence prevention programs work with an emphasis on health workers responsible for the care actions and conduct their work activities into units organized by the logic of spontaneous demand as in the case on emergency and primary healthcare. It is indicated actions to improve working environment and interpersonal relationships among team members and users of health services. It is indicated that the anti-violence institutional programs include actions to improve working environment (furniture, weather conditions, noise control and equipment). Adequacy of management models aimed at strengthening interpersonal relationships between team members and users of health services are key measures of prevention therefore essential in coping workplace violence in health services.